2009
DOI: 10.1093/annonc/mdn559
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for concurrent chemotherapy and radiotherapy of locally advanced lung cancer patients: a prospective, population-based study

Abstract: More than half of patients with stage III lung cancer were theoretically not eligible for concurrent chemoradiation. Less toxic alternatives are needed for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(100 citation statements)
references
References 29 publications
4
92
0
4
Order By: Relevance
“…While in US, pattern of care surveys report the use of concurrent chemoradiation in approximately ¾ of patients, similar studies in EU report lower use of concurrent chemoradiotherapy strategy. For example, De Ruysscher et al reported the results of a populationbased study conducted in the Netherlands in which less than 50% of patients were treated with concurrent chemoradiation [9]. In Italy, the RIGHT3 survey showed little adherence to Italian Association of Medical Oncology Guidelines recommending concurrent chemo-radiation for stage III NSCLC [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in US, pattern of care surveys report the use of concurrent chemoradiation in approximately ¾ of patients, similar studies in EU report lower use of concurrent chemoradiotherapy strategy. For example, De Ruysscher et al reported the results of a populationbased study conducted in the Netherlands in which less than 50% of patients were treated with concurrent chemoradiation [9]. In Italy, the RIGHT3 survey showed little adherence to Italian Association of Medical Oncology Guidelines recommending concurrent chemo-radiation for stage III NSCLC [10].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, according to recent surveys, particularly in Europe [9,10], but also in US [11], in clinical practice sequential chemo-radiotherapy protocols are still used in a large proportion of patients with locally advanced inoperable NSCLC. In this context, little evidence has been produced 5 about the potential benefit of adding chemotherapy concurrently to thoracic irradiation delivered after induction chemotherapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be remembered that the potential toxicity from the concurrent approach can be significant, with population based studies showing that performance status, age and comorbidities exclude a high number of patients from the concurrent form of treatment 7 . The feasibility of adding induction chemotherapy to CHART has also been demonstrated by the INCH trial 17 , results from which suggest this approach is associated with less toxicity than concurrent schedules.…”
Section: Van Baardwijk Et Al Have Performed a Systematic Review That mentioning
confidence: 99%
“…However, the majority of patients are not suitable for this treatment based on poor performance status and co-morbidities 7 . The alternative treatment offered to patients who are unsuitable for concurrent CTRT is sequential CTRT (chemotherapy given prior to RT), but local control rates are inferior when compared to concurrent CTRT which is reflected in worse survival rates 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade there has been a shift to using platinum chemotherapy concurrently with high dose radiation, based on data showing better outcomes when compared with induction chemotherapy [6]. However, this approach is suitable for less than half of patients with locally advanced NSCLC [11,12].…”
Section: Introductionmentioning
confidence: 99%